Analisis Pengaruh Kinerja ESG, Ukuran Perusahaan, dan Profitabilitas terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan FMCG di BEI Tahun 2021–2023) - Chidatolu, Sonya Grace (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to analyze the effect of ESG performance, company size, and profitability on firm value in Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. This research uses a quantitative approach with secondary data obtained from annual reports and financial reports of FMCG companies. Using purposive sampling, this study selected 32 companies from a total population of 86 FMCG companies, resulting in 96 observations. Data were analyzed using multiple linear regression analysis assisted by SPSS version 30. The results show that ESG performance has a negative and significant effect on firm value, company size has a negative and insignificant effect on firm value, while profitability has a positive and significant effect on firm value. These findings indicate that profitability remains an important factor influencing firm value, while ESG performance and company size require further consideration in the context of FMCG companies in Indonesia.